Optimized Production of High-Titer Recombinant Adeno-Associated Virus in Roller Bottles. (January 2003) - Liu, Y.-L.; Wagner, K.; Robinson, N.; Sabatino, D.; Margaritis, P.; Xiao, W.; Herzog, R.W.
Adeno-associated viral (AAV) vectors are used for in vivo gene transfer in a number of preclinical models of genetic diseases (including large-animal models) and are currently being tested in clinical trials for treatment of hemophilia B and cystic fibrosis. Protocols for production of AAV vectors in a helper virus-free system are available and are based on transient transfection of HEK-293 cells with multiple plasmids. Scale-up of vector production has been labor intensive and inefficient because of a lack of larger culture vessels suitable for growth of adherent cells, large-scale transfection, and vector production. Here we report efficient production of AAV vector in roller bottles, which represents a 10-fold scale-up from the conventional flask or plate method. Optimized production yielded greater than 10 13 vector genomes per bottle and was as cost effective as published protocols using plates. Successful vector production by this method was dependent on optimization of transfection by calcium phosphate precipitation, of monitoring of cell growth (by measurement of glucose consumption), of cell culture conditions, and CO2 /air exchange with the culture vessel.